Significance of Pattern of Invasion in Tongue Squamous Cell Carcinoma—A Retrospective Study from a Regional Cancer Center of North-East India - Rhutso, Yopovinu; Kakoti, Lopa M.; Sharma, Jagannath D.; Kalita, Manoj (South Asian Journal of Cancer, 2022)
Introduction Many multiparametric models and scoring systems had been proposed in oral tongue squamous cell carcinoma (OTSCC) to predict the survival and recurrence, out of which pattern of invasion (POI) is gaining focus recently.Objective We conducted a retrospective study with the aim to see the prognostic significance of the POI and other parameters such as depth of invasion, perineural invasion (PNI), and lymph node status in OTSCC.Materials and Methods The slides of already diagnosed OTSCC cases were prepared from January 2015 to December 2017 records and studied by two pathologists for different patterns using Brandwein-Gensler scoring system. The different clinicopathologic parameters were compared with different POI. Statistical analysis was performed to present cumulative survival outcomes and for comparison.Results Most of our patients were > 40 years of age with male preponderance. Tumor differentiation pattern was assessed using Broders' system of grading that showed 85% of tumors were well, 12.5% tumors were moderately differentiated, and 2.5% tumors were poorly differentiated. The worst POI was predominantly pattern III (50%) followed by pattern II (32.5%) and pattern IV (13.8%). Most patients were in stage II (33.8%) followed by stage III (32.5%), stage IV (26.3%), and stage I (7.5%). There was an inverse relationship between POI with tumor stage and recurrence. A strong statistically significant association was found between POI with perineural infiltration and lymph node metastasis.Conclusion We concluded from our study that worst POI is significantly associated with number of lymph nodes metastasis and perineural infiltration and hence can be used as an independent prognostic factor.
Keywords: pattern; invasion; worst; prognostic; tongue; lymph node